Genetic Diversity on Farm in Japanese Paper Mulberry - Dinh Thi Lam; Katsunori Tanaka; Akihiko Takashima; Ayako Shibutani; Ryuji Ishikawa (Ecology and Evolution)
ABSTRACT Paper mulberry is a fiber resource for paper making. Washi, a traditional paper in Japan, has been produced from Broussonetia × kazinoki, a hybrid between B. monoica and B. papyrifera. Elite strains have been vegetatively propagated and distributed within Japan. In this study, these three strains' complete chloroplast (cp) genomes were reconstructed as pseudomolecules consisting of 160,861, 160,868, and 160,878 bp, respectively. They were compared with other database strains to detect insertion/deletion (INDEL) polymorphisms. In total, 25 INDELs were identified in these cp genomes. ISSR‐based MIG‐seq polymorphisms were applied to determine whether varieties or regional groups can be discriminated. Although various types of cultivars exhibiting different appearances are hard to discriminate, principal component analysis (PCA) distinguished two major groups. Maternal lineages reflecting the diverse origins of Japanese paper mulberry were determined using hypervariable maternal markers. An NGS‐oriented nuclear marker system revealed the heterogeneous nature of domesticated paper mulberry, reflecting the complex origins of Japanese B. × kazinoki.